The Assassination of Jacques Lemaigre Dubreuil - Hoisington, William A. (History and Society in the Islamic World, 2005)
This is a political biography of the French industrialist and political activist Jacques Lemaigre Dubreuil (1894-1955), president of the Taxpayers' Federation in the 1930s, entrepreneur in wartime France and Africa, organizer of the 'Group of Five' in Algiers which prepared for the Allied landings in North Africa (November 1942), 'inventor' of General Henri Giraud as a candidate for the leadership of liberated North and West Africa, negotiator of the Murphy-Giraud Agreements and the Anfa Memorandum with President Roosevelt (1942 and 1943), political writer on the postwar future of France in Morocco and the owner of the liberal newspaper Maroc-Presse. He was assassinated in Casablanca by French counter-terrorists in June 1955, a 'turning point' event which pushed the French government to grant independence to Morroco. Was he a rabble-rouser, a demagogue, a betrayer of French interests at home and overseas or a reformer, a patriot, a hero of the anti-German resistance, and a champion of Franco-Moroccan solidarity?